Nursing care for patients with orotracheal tube: evaluation performed at intensive care unit - Lima Aires Gomes, Giselle Pinheiro; Barbosa Rezende, Adriana Arruda; Silva, Íris Lima; Almeida, Joana D’Arc Ponce de Almeida Ponde de; Beresford, Heron (Revista de Enfermagem UFPE on line, 2009)
Objective: to evaluate the care dispensed by the nursing team of the Intensive Care Unit of the Hospital Public of Gurupi to patients using orotracheal tube. Methods: this is about a descriptive, observational research, from quantitative analysis. The observation of care, according to the protocol aimed at the handling of the endotracheal tube, occurred for seven days in March 2009 for 14 hours a day, with a total of 105 hours. The study was approved by the Research Ethics Committee of the University Castelo Branco (0169/2008). Results: checking blood pressure of the cuff every 12 hours and hydration of the lips every four hours was not performed by nursing staff, the oral hygiene was performed only once a day, but was assured by professionals an alternative means of communication intubated patients, the exchange and holding the lace was made daily, the use of gauze on the sides of the oral cavity was placed when it was apparent some aggression to the skin of the patient, the aspiration of endotracheal tube with aseptic technique, was performed to avoid complications. Conclusion: the nursing team observed presented failures in attendance which could be reduced through implanting specific protocols for handling of the orotracheal tube. Descriptors: intubation; nursing care; intensive care unit.